Sistem Pengendalian Manajemen Dan Kepemimpinan Pada Bisnis Keluarga Etnis Minangkabau - Ayu Wandira; Sany Dwita; Erly Mulyani (Universitas Negeri Padang, 2019)
This study's purpose in this paper is to reveal the relationship between management control systems and leadership styles in the Minangkabau ethnic family business. By using an interpretive qualitative approach with the lens of ethical and emicent anthropology. Ethical views refer to outside interpretations (researchers and previous literature). The combination of these two views allows a deep understanding of this case. Interview, observation and documentary analysis used to collect data. and emik is how people interpret phenomena. The emic and ethical approaches are used to see how culture influences leadership styles and management control systems in Minangkabau ethnic family companies. Minangakabau is an ethnic that has special characteristics with the matrilineal system, namely the lineage drawn from the mother's side, and the leadership system known as tungku tigo sajarangan and with traditional jargon adat basandi syarak, syarak basandi kitabullah. The Minangkabau ethnic group is known for its culture of migrating and trading. The cultural background of the leader will determine how the management in the company, but the leader is not the only determinant in the formation of culture, but the leader adapts to the cultural conditions, with the same culture between leaders and employees, the organizational process will run better. The limitation in this study is that this research was only carried out on one Minangkabau ethnic family, so that it was unable toililize all the values ​​applied by entrepreneurs from the Minangkabau ethnic group in the companies they owned.